The Role Of Instagram Social Media As A Public Communication Media At Puskesmas Cilengkrang Kabupaten Bandung - Putri Astiti; Duane Masaji Raharja (STIA Bagasasi, 2023)
Social media used by government agency can act as a medium of communication with the masses, not only by verbal means. Nowdays, government agency on various level have used social media to spread information to the people. They are certainly cannot be detach from Public Communication. Public Communication is a process of delivering messages or interaction with the public where the message can be in a form of education, instruction, or information. Puskesmas is a government agency as a center for development, construction, and service. Also function as vanguard post for developmentof community healthcare services. Therefore, Puskesmas Cilengkrang utilize social mediaas a channelto deliver various information about healthcare. In this case they used Instagram. The role of @pkm_cilengkrang_kabbandung Instagram is to convey information about various government programs and all event held by Puskesmas Cilengkrang Kabupaten Bandung. This research shows that type of information conveyed by Puskesmas Cilengkrang Kabupaten Bandungon Instagram is about government program to support people healthcare, training or workshop event held there, education regarding community healthcare, and also schedule of immunizations or regular vaccinations.